2022
DOI: 10.1242/dev.200263
|View full text |Cite
|
Sign up to set email alerts
|

Microgel culture and spatial identity mapping elucidate the signalling requirements for primate epiblast and amnion formation

Abstract: The early specification and rapid growth of extraembryonic membranes are distinctive hallmarks of primate embryogenesis. These complex tasks are resolved through an intricate combination of signals controlling the induction of extraembryonic lineages and, at the same time, safeguarding the pluripotent epiblast. Here, we delineate the signals orchestrating primate epiblast and amnion identity. We encapsulated marmoset pluripotent stem cells into agarose microgels and identified culture conditions for the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 88 publications
2
3
0
Order By: Relevance
“…8b ). In line with this observation, a high BMP and low NODAL signalling environment has been implicated recently in amnion differentiation of marmoset ES cells 41 and in human ES cells during extraembryonic mesenchyme differentiation 34 , suggesting that similar dynamics may drive differentiation of these populations within inducible human embryo-like structures.
Fig.
…”
Section: Bmp Mediates Epiblast Differentiationsupporting
confidence: 71%
See 1 more Smart Citation
“…8b ). In line with this observation, a high BMP and low NODAL signalling environment has been implicated recently in amnion differentiation of marmoset ES cells 41 and in human ES cells during extraembryonic mesenchyme differentiation 34 , suggesting that similar dynamics may drive differentiation of these populations within inducible human embryo-like structures.
Fig.
…”
Section: Bmp Mediates Epiblast Differentiationsupporting
confidence: 71%
“…Indeed, immunofluorescence analysis demonstrated that the inner, SOX2-positive domain upregulated amnion markers, including CDX2 and ISL1 by day 6 post-aggregation. By day 8 post-aggregation, the inner domain expressed the mature amnion markers VTCN1 and HAND1 39 , 41 (Fig. 3d and Extended Data Fig.…”
Section: Differentiation Within Embryoidsmentioning
confidence: 99%
“…In PSC populations, PAC1 formed a self-interacting source of FGF2 , but far fewer FGF2 -centric interactions were observed in 4i, with CAC2/3 instead appearing to act as a source for FGF1 . Because of differences in the relative proportions of individual clusters in the PSC/4i/PreME samples, this suggests a general decrease in FGF2/3/4 -related interactions in PreME and 4i populations versus PSC, an observation that correlates with previous studies in humans ( Penfold et al, 2018 Preprint ) and rabbits ( Kobayashi et al, 2021 ) suggesting an antagonistic for FGF in PGC competence, with additional roles in PSC proliferation ( Kobayashi et al, 2021 ) and ablation of amnion formation ( Munger et al, 2022 ).…”
Section: Resultssupporting
confidence: 80%
“…We next investigated the specification of epiblast-derived cell populations, specifically focusing on amnion patterning, which forms before gastrulation in primates. Previous studies of non-human primates and human stem cells suggest that amnion induction is dependent on BMP 30 33 , but many functional and molecular features of this lineage remain unclear. Morphologically, hEEs frequently contained ISL1 + cells (a marker of primate amnion 34 ) by D4 to D6, with efficiency ranging from 46.79% to 70.86% depending on the genetic background (Fig.…”
Section: Emergence Of Late Amnion-like Cellsmentioning
confidence: 99%